2019
DOI: 10.1007/s12055-019-00820-3
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric heart transplantation: long-term outcomes

Abstract: Pediatric heart transplant has become the standard of care for end-stage heart disease in children throughout the world. The number of transplants has grown dramatically since the first transplant was performed, and over the last two decades, outcomes have consistently improved with progression in knowledge enhancing the clinical course and outcomes of these patients. Shortterm outcomes in the most recent era have been excellent resulting in a renewed focus towards medium-and long-term outcomes. This article w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 58 publications
(97 reference statements)
3
16
0
Order By: Relevance
“…17 Recently, Westbrook and colleagues suggested to prefer donors not more than 5 years older than the chronological recipient age to avoid poor outcomes including frequent onset of CAV. 6,15 In 2020, Conway and colleagues' meta-analysis of the characteristics of the ideal donor in pediatric heart transplantation, they found that the DRWR should be between 0.7 and 3 and that donor age should be <50 years old. 5 That same year, the ISHLT published a consensus statement describing donor organ acceptability criteria for pediatric heart transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…17 Recently, Westbrook and colleagues suggested to prefer donors not more than 5 years older than the chronological recipient age to avoid poor outcomes including frequent onset of CAV. 6,15 In 2020, Conway and colleagues' meta-analysis of the characteristics of the ideal donor in pediatric heart transplantation, they found that the DRWR should be between 0.7 and 3 and that donor age should be <50 years old. 5 That same year, the ISHLT published a consensus statement describing donor organ acceptability criteria for pediatric heart transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The ISHLT reported in 2017 that the greatest risk of death is in the first-year post heart transplant, and those patients who survived the first year had a median survival of more than 15 years. 14,15 In 2003 Razzouk et al 8 analyzed the effect of oversize pediatric heart transplantation and concluded that the common morbidities of cardiac transplantation and long-term survival of children with complex congenital heart disease are not adversely influenced by the use of oversized cardiac allografts. Tang et al 16 focused on the issue of low DRWR and showed that despite smaller organs, patients did not have longer inotropic support or higher short-term mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretically, the best way to treat CAV is to prevent it from occurring; however, this is only hypothetical as despite many approaches being evaluated, little insight has been gained into the most effective approach or strategy to achieve true prevention. Transplant recipients with known risk factors for atherosclerosis and/or CAV in specific should be closely monitored post‐transplant with a focus on modification of risk factors and opportunities for early interventions 3,23 . From a medication standpoint, statins have been shown to play a beneficial role in slowing the development of CAV.…”
Section: Management Of Cavmentioning
confidence: 99%